2013
DOI: 10.1038/nature12172
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals bimodality in expression and splicing in immune cells

Abstract: Recent molecular studies have revealed that, even when derived from a seemingly homogenous population, individual cells can exhibit substantial differences in gene expression, protein levels, and phenotypic output1–5, with important functional consequences4,5. Existing studies of cellular heterogeneity, however, have typically measured only a few pre-selected RNAs1,2 or proteins5,6 simultaneously because genomic profiling methods3 could not be applied to single cells until very recently7–10. Here, we use singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
1,114
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,151 publications
(1,162 citation statements)
references
References 31 publications
44
1,114
4
Order By: Relevance
“…This was initially done using microarrays 10,11 but is more often now done using next-generation sequencing [12][13][14][15] . Such approaches have been used to model early embryogenesis in the mouse 16 and to investigate bimodality in gene expression patterns of differentiating immune cell types 17 .…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…This was initially done using microarrays 10,11 but is more often now done using next-generation sequencing [12][13][14][15] . Such approaches have been used to model early embryogenesis in the mouse 16 and to investigate bimodality in gene expression patterns of differentiating immune cell types 17 .…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…Both the huge cell‐to‐cell variability and the amount of data these new technologies have brought to light constitute a great resource and at the same time a challenge for scientists. The parallel development of more sophisticated algorithms, faster computational approaches and new data visualization methods has already allowed scientists to gain new insights into immune system diversity 18, 23, 55, 56. Despite this incredible progress, there are still some issues that need to be solved and most of the works involving single‐cell sequencing are methodological.…”
Section: Resultsmentioning
confidence: 99%
“…Genes with higher transcriptional bursts and lower frequency are noisier than genes that are expressed in small frequent bursts 54. An scRNA‐seq based study of bone marrow‐derived dendritic cell activation revealed that certain genes had a bimodal pattern of gene expression 55. Subsequent studies showed that paracrine signalling of a subset of fast‐responding dendritic cells affects the whole population 56.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the field of systems immunology, single-cell transcriptomic profiling (RNA-seq) is an experimental technique that has proven effective for delineating molecular heterogeneity within immune cell subtypes. 2 Large-scale genomic techniques like single-cell RNA-seq are often described as hypothesis generating. One of the challenges of applying these experimental techniques is shortening the progression from hypothesis generation to hypothesis testing.…”
mentioning
confidence: 99%